Management by competencies and its relationship with the work environment in a services, consulting and outsourcing company, Lima, Peru - Rey de Castro Hidalgo, Daniel Enrique (2020)
The main objective was to determine the level of relationship between a skills management model and the work environment of workers in a service, consulting and outsourcing company. The population was 350 workers from a Peruvian company with an adjusted sample of 120 to 95% confidence level. The analysis methods are carried out through surveys with two types of scale, Likert type and dichotomous. According to the results of the variable management by competences and the work environment, the difficulties and the positive form are correlated (0.622). The dimensions of variable management by competences are: planning and dissemination of the strategic plan, identification of competencies, basic training in competencies and work environment. An application scheme of a competency management model is proposed. It is concluded that competency management and all its dimensions are related to the work environment Key words: Competences, strategic plan, leadership, work environment.